REGAT: A permanent GPS network in Algeria, configuration and first results. Issue 4 (April 2019) - Yelles-Chaouche, Abdel Karim; Lammali, Kamel; Bellik, Amar; Bougrine, Amina; Mahsas, Abdel Hakim; Bacha, Wahab; Terki, Toufik; Meliani, Othmane; Ouzzani, Fares; Lakehal, Yacine; Ait Amir, Ahcene; Khellaf, Kamel; et al.
Abstract: The REGAT ( "REseau Géodésique de l'ATlas" ) geodetic network is composed of 53 continuously–recording GPS stations distributed in the Algerian Atlas. It spans the whole width of the Algerian coast and reaches 300 km inland, with inter-sites distance of about 100 km. One additional site is located in Tamanrasset in the southernmost part of the country. The network, whose oldest stations started operating in 2007, encompasses the main active tectonic features of the most seismically active segment of the Nubia-Eurasia plate boundary in the Western Mediterranean. Here we describe the network configuration, the data collection and analysis strategy, as well as some preliminary results on horizontal GPS velocities. A detailed analysis of the velocity field in terms of plate boundary kinematics is the topic of a separate publication. The REGAT network fills an important gap in our knowledge of present-day plate boundary deformation in the Western Mediterranean. It will soon be enhanced by an additional 100 sites in order to improve deformation monitoring with a higher spatial resolution for a better assessment of the regional seismic hazard.